PENERAPAN LATIHAN PILATES UNTUK MENGURANGI NYERI MENSTRUASI PADA REMAJA PUTRI - Putri Nursanti Strada, Devy; Puji Kumalasari, Eri (Jurnal LENTERA, 2024)
Dysmenorrhea is a disorder of menstrual blood flow or menstrual pain that, if not promptly addressed, can affect an individual's mental and physical functions, necessitating non-pharmacological interventions. One such non-pharmacological therapy is Pilates exercises, which relax contracted muscles and stimulate the hypothalamus to produce endorphins, a natural pain reliever that reduces pain. This community service activity aims to reduce menstrual pain in adolescent girls through Pilates exercise classes held in Dusun Luksongo, Tugurejo Village, Ngasem District, Kediri Regency. The program involves 10 adolescent girls as participants. The methods used include socialization, education, and training in Pilates techniques by a competent instructor. The training includes practical guidance on safe and effective Pilates techniques to reduce menstrual pain and enhance the well-being of the adolescent girls. The results of the service show that out of 10 adolescent girls who participated in the program, 8 girls (80%) reported a decrease in menstrual pain after attending the Pilates sessions, while 2 girls (20%) reported the pain remained the same. No participants reported an increase in pain. These results indicate that the Pilates exercise classes have a significant impact on reducing menstrual pain in adolescent girls, which is an important factor for their well-being. Therefore, the Pilates exercise class program can be considered effective in reducing menstrual pain and improving the physical and psychological health of adolescent girls, as well as strengthening their role in maintaining their own health.